ANALISIS PENGARUH NIM, NPL, CAR, CR, LDR DAN KAP TERHADAP KINERJA KEUANGAN BANK DI INDONESIA (Periode 2007-2010) - Anwar, 11.42.02.0070 (Students Journal of Economic and Management, 2013)
This research aim to analyze the influence of Net Interest Margin (NIM), Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Cash Ratio (CR), Loan To Deposit Ratio (LDR), Kualitas Aktiva Produktif (KAP) on the financial performance (ROA) of the general banking in Indonesia. Samples of this research was taken in the 71 banks which publishingÂ  financial report from 2007 up to 2010, the data analyzed by multiple regression test whith normality test and the assumption of casssical test by multicollinerrity, autocorrelation and heteroscadasticity than hypothesis test by f-test and t-test, also test of coefficient determinations. The results is known that variable NIM, CAR, KAP has positive significant influence to ROA than NPL, CR has negative significant influence to ROA and variable LDR hasnegativeÂ  not significant to ROA at 5% confidence level. Keywords: Return On Asset (ROA), Net Interest Margin (NIM), Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Cash Ratio (CR), Loan To Deposit Ratio (LDR), Kualitas Aktiva Produktif (KAP)